Os desafios da "indústria 4.0" na Zona Franca de Manaus - Lopes, Ítalo Lira (Brasil, 2023)
The Industry 4.0 has become an increasingly constant topic in the business and industrial world due to all its technological innovations of interconnecting and reading data in order to boost production and generate more gains for the firm. However, the implementation of the innovations has thrown up a number of challenges that both the country and the industry itself need to understand and solve. Given the inequality and concentration of industry in the Southeast region that has surrounded Brazil throughout its industrial and economic formation, it has only hindered the challenges that geographically distant regions, such as the North, will have to face to enter the fourth revolution. The Manaus Free Trade Zone is then created to supply all the difference and concentration of industries, income, and population. Thus, with the advent of revolutions throughout the industrial formation and the most recent revolution 4.0, this paper seeks to identify what challenges the ZFM (The Manaus Free Trade Zone) must go through to effectively enter the new era of industry beyond the social and economic opportunities that the insertion of Industry 4.0 should bring to the northern region. Thus, the research aimed to analyze the industrial development of the industrial center of the North region, the Manaus Industrial Pole which is in the Manaus Free Trade Zone model with a focus on the challenges and prospects of implementing Industry 4.0 in the production mode through bibliographic research being used scientific articles, journalistic articles and interviews, books, among other bibliographic materials and analyzed by methods appropriate to the type of research, as theoretical historical method, descriptive and analytical theoretical, and descriptive quantitative. Resulting thus in a better understanding of the history and importance of the great industrial revolutions in developed countries, compared to Brazil, which originated the innovative ideas of Industry 4.0 and great challenges of implementation in geographically distant regions such as the MFTZ, with high implementation costs, scarce skilled labor, uncertainty about the possibility of increasing unemployment, among other factors. But good prospects were also identified regarding the implementation of technological advances, through various projects, investments, cooperation between public and private initiative, and indicators of employability, costs and revenues behaving in a directly proportional way, thus demonstrating an interesting and favorable path to Industry 4.0 in the Manaus Free Trade Zone.